Effects of different types of exercise on hypertension in middle-aged and older adults: a network meta-analysis - Gao, Wei; Lv, Moran; Huang, Tao (Frontiers in Public Health, 2023)
Objective This study mainly used network meta-analysis to explore the effect of different types of exercise on hypertension in middle-aged and older adults. Methods Several databases (e.g., PubMed, Embase, and the Cochrane Library) were used to search for randomized controlled trials on the effects of different types of exercise on hypertension in middle-aged and older adults. Results A total of 19 articles and 2,385 participants were included in the analysis. Aerobic exercise interventions [MD = −9.254, P < 0.05, 95% CI (−14.810, −3.698)] and static exercise interventions [MD = −10.465, P < 0.05, 95% CI (−18.135, −2.794)] had a significant effect on the improvement in systolic blood pressure (SBP). For diastolic blood pressure (DBP), aerobic exercise interventions [MD = −1.4096; P > 0.05, 95% CI (−8.2395, 5.4201)] and static exercise interventions [MD = −4.5206, P > 0.05, 95% CI (−14.0436, 5.0023)] were not statistically significant. The results of the surface under the cumulative ranking curve (SUCRA) showed that static exercise improved hypertension better than aerobic exercise. Conclusion Aerobic exercise and static exercise have been shown to have a good effect on the improvement of hypertension, but the effect on DBP is not significant.